2022
DOI: 10.1038/s41598-022-15051-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anticancer effects of carboplatin–gelatin nanoparticles in different sizes synthesized with newly self-assembly method by exposure to IR light

Abstract: Carboplatin (CP), a platinum analog, is one of the most widely used chemotherapeutic agents in the treatment of colorectal cancer. Although platinum-based drugs are quite effective in anticancer treatments, their use in a wide spectrum and effective treatment possibilities are limited due to their systemic side effects and drug resistance development. In recent years, studies have focused on increasing the therapeutic efficacy of platinum-based drugs with drug delivery systems. Gelatin, a protein, obtained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The Ge-NPs have multiple physicochemical properties, such as surface charge influence, size, shape, drug delivery efficiency, therapeutic release kinetics, in vivo circulation time, and metabolic activity. 34 We evaluated the particle size, entrapment…”
Section: Resultsmentioning
confidence: 99%
“…The Ge-NPs have multiple physicochemical properties, such as surface charge influence, size, shape, drug delivery efficiency, therapeutic release kinetics, in vivo circulation time, and metabolic activity. 34 We evaluated the particle size, entrapment…”
Section: Resultsmentioning
confidence: 99%
“…Two dropsample was deposited onto a glass slide, and allowed to dry at room temperature. Afterwards, the sample was coated with gold under vacuum to make it electrically conductive, then it was examined by FESEM [23] .…”
Section: Characterization Of Tc-shdl Characterization Of Size and Mor...mentioning
confidence: 99%
“…Thus, several studies have been reported on the nanoformulation of Cr in an attempt to improve its pharmacokinetics properties and pharmacological activity while minimizing its toxic effects. 10 Finding a solution for the rapid CRC development and the devastating side effects of the commonly used therapeutic agents became an obligate need. One of the recent strategies used is developing nanoparticles (NPs) for many purposes, like drug delivery, imaging, and diagnosis.…”
Section: Introductionmentioning
confidence: 99%